Economic Effect of Coronavirus (COVID-19) Outbreak on Airline Businesses. - Alıcı, Abdulkadir; Polat, Leyla (Electronic Turkish Studies, 2020)
As a result of the COVID-19 pandemic, as of June 30, 2020, there are 10 million cases and 510 thousand people have died. Many countries had to suspend airline flights due to the pandemic. Airline businesess have had to reduce their flights due to the countries' banning flights and the decrease in passenger airline demand. Although some countries, especially the USA, provide financial support to airline businesess, all airline businesess worldwide suffer great losses in this process. The main purpose of this study is to reveal the relationship between the share prices of airline companies and the COVID-19 pandemic. The dependent variable of this research is the stock price (ASP), the independent variables of this research are the number of case (CASE) and number of deaths (DEATH) of the countries that suffer from COVID-19. After that, daily data between 25.02.2020 - 30.06.2020 has been used for our research topic. At the same time, 9 airline companies have been chosen among the countries that have the highest number of cases. As a result of the panel data analysis conducted according to the constant effects, it has been determined that the CASE variable has a negative effect on ASP by a 5% significance level. And similarly, the DEATH variable has a negative effect on ASP by a 10% significance level. According to this result, it is seen that the deaths caused by the Coronavirus pandemic negatively affected the share prices of airline companies. From this point of view, COVID-19 affects the stock prices of airline companies negatively and, thus it is an economic proof of the crisis experienced in the airlines.